Analysis of the Factors Affecting Banking Profitability in Bangladesh (Global Journal of Management and Business Research, 2019)
The banking sector of Bangladesh is one of the major contributors to the Bangladesh economy with the commercial sector playing a vital role in the financial sector. This paper investigates the impact of bank-specific variables on bank profitability in Bangladesh from 2011-2017. For this purpose, the data of 30 banks are collected. Correlation, regression analysis and time series analysis are done with the collected data of the 30 banks. ROA is taken as representatives of bank's profitability i.e. this is the dependent variables. Non-performing loans, Loan to Deposit Ratio, Equity to Asset ratio and Interest Expense to Income ratio are taken as independent variables to find out what are the effects of these variables on profitability. From the correlation analysis, we have found that if LDR, NIE-INC and EQUITTA increase, ROA also increases. Whereas, increase in NPL results in decrease of ROA. We established one regression model in terms of profitability, considering the other variables as independent variables. This paper also mentions the current banking condition of Bangladesh and how important banking sector is, for its economy.
Keywords: major contributor; bank profitability; ROA; NPL